Multi-criteria acces selection mechanism based on user preferences in heterogeneous wireless networks - Xiaoxue, Guo (2023)
Access selection is one of the key technologies in heterogeneous wireless network. At present, the access selection technology mainly adopts single and common network performance parameter as access selection criteria, ignoring the user preferences. It easily leads to access selection schemes that are out of line with the actual user requirements, and it does not improve user experience. In this thesis, a multi-criteria access selection mechanism supporting service characteristics and user preferences is designed. This mechanism uses utility function, entropy method, FAHP, and fuzzy logic theory to calculate the utility value, objective weight, subjective weight, and score of network attributes, respectively. FAHP is implemented to determine user preference values, and MADM method is used to establish the comprehensive candidate networks scores. The simulation experiments show that the proposed mechanism enables users to choose the most suitable network, achieve higher gain and reduce handover between different networks compared to other access selection algorithms. The proposed mechanism can support the diversity of service characteristics and user preferences at the same time, and is suitable for user centric next-generation mobile Internet application scenarios.